If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2d + -3 = 10 Reorder the terms: -3 + 2d = 10 Solving -3 + 2d = 10 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2d = 10 + 3 Combine like terms: -3 + 3 = 0 0 + 2d = 10 + 3 2d = 10 + 3 Combine like terms: 10 + 3 = 13 2d = 13 Divide each side by '2'. d = 6.5 Simplifying d = 6.5
| (x-5)(x+11)= | | (kx^2)+(-10k-6)(x)+108=0 | | x^2-2xy-y^2=14 | | kx^2+(-10k-6)x-108=0 | | -[7(a+2b)+4b]= | | 2y+15=7y | | 2x-x^3=-5 | | 5(x^2)-2x-45=0 | | Ab+Ba+ca=abc | | 18x+36=8x^2+50x+32 | | 1+8(-x+10)=9 | | 2(2x^2+y^2)dx+(2xdy+y)dy=0 | | Tn=3n-2 | | 9-2a+8a= | | 5ln(2)-6ln(3)= | | 0.25x^3=1 | | 2+2(-9+4x)=10x-8 | | 5(l+2)=-40 | | 5bc+2bc= | | 19x=-13 | | M=k-x | | n^2-2n-35=28 | | n^2-2n-35=7 | | 2t^2-t-5=0 | | n^2-2n-35=14 | | 4x^3-81x^2+162x-81=0 | | -50=-20t-4.9t^2 | | (x+5)(x-7)=14 | | -50=-20-4.9t^2 | | 4tan^2=1 | | 4j+3-3j=10 | | 4j+3c-3j=10 |